Anxiety sensitivity and working memory capacity: Risk factors and targets for health behavior promotion. (November 2016) - Otto, Michael W.; Eastman, Abraham; Lo, Stephen; Hearon, Bridget A.; Bickel, Warren K.; Zvolensky, Michael; Smits, Jasper A.J.; Doan, Stacey N.
Abstract: Understanding the nature and influence of specific risk profiles is increasingly important for health behavior promotion. The purpose of this article is to document the value of two factors—anxiety sensitivity (AS) and working memory capacity (WMC)—for enhancing risk for the initiation and/or maintenance of a range of negative health behaviors. AS is a distress-related risk factor that potentiates avoidance/coping motivations for negative health behaviors. Stress provides the conditions for negative somatic and affective states, and AS amplifies the aversiveness of these experiences and correspondingly hinders adaptive functioning. In contrast, low WMC is hypothesized to exert its effect by decreasing the capacity to filter out current temptations, attenuating a focus on longer-term goals and impairing the application of relevant coping skills at times of stress. In this review, we provide conceptual models for the separate roles of high AS and low WMC in negative health behaviors, review the influence of these factors on specific health behavior exemplars (eating behaviors/obesity, physical activity, smoking, alcohol use, and sleep promotion), provide preliminary evidence for their value as independent treatment targets for health-behavior promotion, and encourage specific research directions in relation to these variables. Highlights: AS and WMC are linked to a wide range of negative health behaviors. Both are modifiable by intervention, with beneficial effects on health behaviors. These documented risk factors warrant additional research and clinical attention.